Thermal and mineral waters - Kumar, Manoj (SCITUS Academics LLC, 2016)
Mineral water is water from a mineral spring that contains various minerals, such as salts and sulfur compounds. Mineral water may be effervescent (i.e., "sparkling") due to contained gases. Traditionally, mineral waters were used or consumed at their spring sources, often referred to as "taking the waters" or "taking the cure," at places such as spas, baths, or wells. The term spa was used for a place where the water was consumed and bathed in; bath where the water was used primarily for bathing, therapeutics, or recreation; and well where the water was to be consumed. Thermal analysis plays a specific role in the identification and quantitative determination of mineral components of rocks. In spite of the fact that minerals were the first group of materials studied regularly by using thermoanalytical methods, the potential offered by these methods is still not fully utilized in the field of earth sciences. The range of thermoanalytical methods applied in earth sciences is rather wide. Most works are based on DTA. DTA data provide indirect analytical information on a material and the quantification of a reaction is limited.